2017
DOI: 10.5812/hepatmon.58022
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Genotype 1 Virus C Compensated Liver Cirrhosis in the Era of Directly Acting Antiviral Therapy

Abstract: Objectives: The current study aimed at evaluating the association between metabolic syndrome (MeS) in patients with hepatitis C virus (HCV) liver cirrhosis (compensated, genotype, 1b) and changes after sustained viral response (SVR) following a 12-week therapy with paritaprevir, ritonavir, ombitasvir, dasabuvir, and ribavirin (PrOD+R). Methods: The current multicenter retrospective study included 809 patients diagnosed with compensated HCV cirrhosis (child class A), all 1b genotype treated for 12 weeks with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Among the studies that showed an increase in HDL, it appears to be consistent after the viral eradication, whereas during treatment HDL declined 13,91,96 . Higher baseline fibrosis, female sex, and the presence of metabolic syndrome seem to be the factors related to the increase in HDL after SVR 22,45,46,64,72,95 . On the other hand, a low fibrosis stage was associated with a reduction in HDL 61 .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Among the studies that showed an increase in HDL, it appears to be consistent after the viral eradication, whereas during treatment HDL declined 13,91,96 . Higher baseline fibrosis, female sex, and the presence of metabolic syndrome seem to be the factors related to the increase in HDL after SVR 22,45,46,64,72,95 . On the other hand, a low fibrosis stage was associated with a reduction in HDL 61 .…”
Section: Resultsmentioning
confidence: 90%
“…Baseline insulin and HOMA‐IR were greater in cirrhotic patients compared to noncirrhotic ones 28,54 . After SVR, cirrhotic patients showed a significant reduction in IR, fasting glucose, 21,52,61,72 HbA1c, 62,73 and 2‐h plasma glucose 74 . The amelioration of glycemic parameters in cirrhotic patients seems to be irrespective of BMI and the presence of T2DM, 74 but after SVR, they showed higher HOMA‐IR values compared to patients without baseline advanced fibrosis 58 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite significant progress in recent years, the etiology of ulcerative colitis (UC) remains poorly understood [1,2]. Likewise, the pathological mechanisms are not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is a potentially severe chronic inflammatory condition of the colon, characterized by periods of activity and remission, with incompletely elucidated etiopathogenesis, in which the immune system interacts with microbiota disorders and/or environmental factors in genetically predisposed individuals [1]. The clinical picture in UC is determined by the extent of the disease and the severity of the inflammation, characterized by the presence of diarrhea and rectal bleeding [2].…”
Section: Introductionmentioning
confidence: 99%